Assessing Technical Efficiency of the Indian Higher Education: An Application of Data Envelopment Analysis Approach. (July 2021) - Kaur, Harpreet
Due to resource constraints in the Indian education sector, efficiency assessment of the higher education is more essential for the proper allocation and the effective utilization of financial and human resources. Moreover, much of the research in the higher education sector has mainly focused on the quality of education and ignored the role of efficiency. Therefore, the present study analyzes the technical efficiency of the higher education in the Indian states. Secondary data for the study were collected from reports of the Ministry of Human Resource Development (MHRD), UGC Reports, Economic Survey of India and Reports of the All India Survey on Higher Education (AISHE). Data Envelopment Analysis was used to analyze the data. The efficiency results suggest that the states analyzed in this study are operating at a moderate level of efficiency relative to each other.